Pemberdayaan Petani Milenial Melalui Pengolahan Limbah Ternak Kelinci menjadi Pupuk Organik Cair: Empowering Millennial Farmers Through Processing Rabbit Livestock Waste into Liquid Organic Fertilizer - Murrinie, Endang Dewi; Arini, Nindya; Widyastuti, Winda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The agricultural sector is an important sector that contributes to economic growth of 13.28%. However, the farm industry is currently experiencing an imbalance in the age of farmers because most farmers have reached old age, the number of farmers aged 19-39 years (millennial farmers) is only 21.93%. In addition, the occurrence of climate change also affects land productivity. One way to reduce climate change is to use organic fertilizers to reduce chemical fertilizers. The purpose of the activity is to increase and strengthen the capacity of the Pagar Bersemi Young Farmers Group through the use of rabbit livestock liquid waste into rabbit urine liquid organic fertilizer to increase land productivity and realize sustainable agriculture. The activity was carried out through (1) socialization of rabbit livestock waste processing technology into rabbit urine liquid organic fertilizer; (2) training in rabbit livestock waste processing technology into liquid organic fertilizer; (3) mentoring and evaluation; and (4) activities for program sustainability. The results of the activity showed that (1) increasing the knowledge and skills of partners about processing rabbit livestock liquid waste into liquid organic fertilizer, (2) partners can process rabbit livestock liquid waste into rabbit urine liquid organic fertilizer.